2020
DOI: 10.1002/jso.25892
|View full text |Cite
|
Sign up to set email alerts
|

Cattell‐Braasch maneuver facilitates the artery‐first approach and complete excision of the mesopancreas for pancreatoduodenectomy

Abstract: How to cite this article: Akita M, Yamasaki N, Miyake T, et al.Cattell-Braasch maneuver facilitates the artery-first approach and complete excision of the mesopancreas for pancreatoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…11 Also, it presents some advantages for pancreatic cancer resection: allows a better exposure of the operating field and a better bleeding control in case of an accident, allows an easier mesopancreas dissection, including the division of the inferior pancreaticoduodenal artery and lymph nodes retrieval. 8,12 The importance of total mesopancreas excision during pancreaticoduodenectomy was recently highlighted and it has been reported as primary site for R1 resection in pancreatic head cancers, then total mesopancreas resection is mandatory for obtain R0 resection. [13][14][15] Another advantage is represented by an easier assessment of a possible neoplastic SMA involvement in the beginning of the operation and the resulting decrease of unnecessary resections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Also, it presents some advantages for pancreatic cancer resection: allows a better exposure of the operating field and a better bleeding control in case of an accident, allows an easier mesopancreas dissection, including the division of the inferior pancreaticoduodenal artery and lymph nodes retrieval. 8,12 The importance of total mesopancreas excision during pancreaticoduodenectomy was recently highlighted and it has been reported as primary site for R1 resection in pancreatic head cancers, then total mesopancreas resection is mandatory for obtain R0 resection. [13][14][15] Another advantage is represented by an easier assessment of a possible neoplastic SMA involvement in the beginning of the operation and the resulting decrease of unnecessary resections.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the Cattell‐Braasch maneuver is easy to perform, it is not associated with morbidity and allows a safe and tension free direct venous anastomosis independently of the length of the segment to be resected 11 . Also, it presents some advantages for pancreatic cancer resection: allows a better exposure of the operating field and a better bleeding control in case of an accident, allows an easier mesopancreas dissection, including the division of the inferior pancreaticoduodenal artery and lymph nodes retrieval 8,12 . The importance of total mesopancreas excision during pancreaticoduodenectomy was recently highlighted and it has been reported as primary site for R1 resection in pancreatic head cancers, then total mesopancreas resection is mandatory for obtain R0 resection 13‐15 .…”
Section: Discussionmentioning
confidence: 99%
“…Accurate knowledge of peripancreatic surgical anatomy can be extracted from a number of very important, recently published clinical [6,[25][26][27] and radiologic studies [28,29]. The latter, nicely describe the anatomy of peripancreatic and proximal jejunal vessels using three-dimensional computed tomography imaging.…”
Section: Vascular Anatomy Of the Mesopancreasmentioning
confidence: 99%
“…2 Our finding that the Cattell-Braasch maneuver could harvest more lymph nodes around the SMA than standard pancreatectomy also indicated that this technique contributed to complete mesopancreas resection. 3 Further research is needed to ascertain whether it is necessary to distinguish the "mesopancreas-first" from the "artery-first" approach, because the mesopancreas includes SMA branches such as the IPDA and J1a.…”
Section: To the Editormentioning
confidence: 99%